Răspuns :
6x = 9
x = 9/6
x = 3/2
9x = 6
x = 6/9
x = 2/3
40 = 25x
x = 40/25
x = 8/5
5x = 15/8
x = (15/8):5
x = (15/8)x(1/5)
x = 3/8
x = 9/6
x = 3/2
9x = 6
x = 6/9
x = 2/3
40 = 25x
x = 40/25
x = 8/5
5x = 15/8
x = (15/8):5
x = (15/8)x(1/5)
x = 3/8
6x=9
x=9/6
x=3/2 simplificam cu 3
9x=6
x=6/9
x=2/3 simplificam cu 3
40=25x
x=40/25 simplificam cu 5
x=8/5
5x=15/8
x= (15/8)/5
x= 15/8 · 1/5
x= 15/40 simplificam cu 5
x= 3/8
/=supra
x=9/6
x=3/2 simplificam cu 3
9x=6
x=6/9
x=2/3 simplificam cu 3
40=25x
x=40/25 simplificam cu 5
x=8/5
5x=15/8
x= (15/8)/5
x= 15/8 · 1/5
x= 15/40 simplificam cu 5
x= 3/8
/=supra